Weed management in wheat (Triticum aestivum L.) under peninsular India - Ghosh, Sourav; Wali, S.Y.; Datta, Debarati (Annals of Agricultural Research, 2018)
A field experiment was conducted during Rabi season of 2014-15 at farmer's field at Vijayapur,Karnataka to study the performance of pre-emergence (pendimethalin 1.0 kg a.i./ha, metribuzin175 g a.i./ha) and post-emergence (2,4-D 2 kg a.i./ha, metsulfuron methyl 4.0 g a.i./ha) herbicideson weed dynamics, crop growth and yield of irrigated wheat. Unchecked weed growth caused25.04% reduction in grain yield of wheat. Better monocot weed control was obtained withpendimethalin fb one intercultivation at 30 DAS and metribuzin fb by one intercultivation at 30 DASwhereas dicot weed count and total weed dry weight were significantly lower with pendimethalinfb metsulfuron methyl and pendimethalin fb 2,4-D. At harvest, pendimethalin fb metsulfuron methylrecorded ~ 29% increase in total dry matter production (7.18 g/plant) and increased the crop N, P,K uptake by 32.3, 53.3 and 34.5% respectively as compared to weedy check. Grain yield wassignificantly higher in weed free check (4.3 t/ha) and was at par with pendimethalin fb metsulfuronmethyl,pendimethalin fb 2,4-D and pendimethalin fb one intercultivation at 30 DAS.